The Use of Liquid Latex to Recover Latent Fingerprints that are Covered in Debris from Exterior Glass Surfaces of Vehicles. Issue 6 (18th August 2020) - Kapsa, Cassandra; Ho, Michael; Libby, Meadow
Abstract: The purpose of this research is to determine if latent fingerprints deposited on the exterior glass surfaces of vehicles, then covered in debris, can be recovered. Past research used liquid latex to lift soot to recover trace evidence. Recently, liquid latex has been used to recover latent fingerprints along the bottom of vehicles. In this study, a total of 216 latent fingerprints were deposited on the exterior windows of three vehicles. Three control and three experimental latent fingerprints were placed on each side window. The vehicles collected debris for either 2, 3, or 4 weeks. After debris collection, liquid latex was applied to the experimental sections. The underlying fingerprints were developed with white granular powder. Control fingerprints were developed directly with white granular powder. A chi‐square test revealed a significant difference in fingerprint recovery between the control and liquid latex method (X 2  = 9.026, d.f. = 1, p  = 0.003). An odds ratio determined that the control method increases the probability of latent fingerprint recovery by 2.68. Fisher's exact test indicated that there is no statistically significant difference between the detail of the recovered control and experimental fingerprints ( p  = 0.065). This study demonstrates that recovery of fingerprints is possible using the liquid latex method; however, the control method recovers more fingerprints on the glass exterior of vehicles. If latent fingerprints are thought to be present on the exterior glass surfaces of vehicles, the control method should be used to improve vehicle processing by investigators.